A photo-elicitation study of homeless and marginally housed Veterans' experiences with patient-centered care - Samuel Sestito; Keri Rodriguez; Kristina Hruska; James Conley; Michael Mitchell; Adam Gordon (The Beryl Institute, 2018)
As part of a qualitatively-driven mixed-methods study, this analysis aimed to describe Veterans Affairs (VA) Homeless Patient Aligned Care Team patients' experiences with patient-centered care. Veterans participated in audio-recorded, semi-structured photo-elicitation interviews about their health and VA health care. Transcripts were analyzed by two coders using template analysis. In 31/36 interviews, 19/20 participants discussed patient-centered care. Veterans noted Picker's Patient-Centered Care Principles; 1) access to care, 2) respect for patient-centered values, preference and expressed needs, 3) information, communication, and education, and 4) coordination and care integration were most commonly discussed, followed by 5) physical comfort, 6) transition and continuity, 7) emotional support and alleviation of fear/anxiety, and 8) family and friend involvement. They also identified 1) quality care and 2) being present with patient as central to patient-centered care. Improvement suggestions included the patient-provider relationship, VA services, and transportation. Photo-elicitation may be useful in understanding patient preferences, needs, and values to ensure patient-centered care delivery.